Prevalence of Rifampicin Resistant Mycobacterium tuberculosis by Genexpert Assay among Presumptive Pulmonary tuberculosis Patients in Dhulikhel Hospital, Nepal - Ranjit, Srijana; Maskey, Sunima; Lodh, Sanjay (Nepal Mediciti Medical Journal, 2025)
BACKGROUND Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB) is a preventable disease but the rise of drug-resistant TB has become a major challenge for its control. Rifampicin resistance, a key marker of multidrug-resistant TB (MDR-TB), can be rapidly detected by GeneXpert MTB/RIF assay. The objective of this study was to determine the prevalence of tuberculosis and rifampicin-resistant/multidrug-resistant Mycobacterium tuberculosis among presumptive pulmonary tuberculosis patients in Dhulikhel hospital.METHODS A hospital-based cross-sectional study was conducted from May to July 2024 among 345 tuberculosis suspected patients whose sputum sample was processed for GeneXpert MTB/RIF assay using standard procedures. Statistical analyses, including chi-square and logistic regression were performed to assess associations between patient characteristics and TB positivity or rifampicin resistance.RESULTS In 345 participants, 30 (8.7%) tested positive for Mycobacterium tuberculosis. Among them, 25 (83.3%) were male and 5 (16.7%) were female. Rifampicin sensitivity was detected in 26 cases (86.7%), resistance in 1 case (3.3%) and indeterminate results in 3 cases (10%). TB positivity was more frequent among older adults (≥40 years), with the highest prevalence in males. The only rifampicin-resistant case was observed in a female aged 15–39 years.CONCLUSION The study indicates that TB is a public health problem in Nepal, mostly affecting elderly and male populations. Detection of resistance to Rifampicin indicates the need for timely diagnosis, regular monitoring for drug-resistance and efficient TB control measures. The GeneXpert assay has been proven to be effective in rapidly detecting TB and Rifampicin resistance in low-resource settings.